On The Effectiveness Of Blended Learning Technologies In Higher Education - K. Lukhmanova, Gulnar; V. Mishchenko, Vitalii; Chsherbovskikh, Irina; Zharbulganovna Yerzhanova, Gulnur; Shmidt, Mariya; Muratbekovna Alimzhanova, Zhanna (Opción, 2019)
The paper highlights the advantages of using blended learning models as one of the trends in higher education system of today. The focal points of the article are the theoretical aspects of the “blended learning” concept, the advantages and disadvan- tages of full-time offline learning and e-learning, the various types of digital educa- tional resources and online services implemented in blended learning models. The key aspects of the paper are the most widely-spread blended learning models used in foreign universities. The main findings of the paper indicate that with the under- standing of proper and adequate application, blended learning effectively forms valuable personal qualities.